A statistical approach for the prediction of cutting forces in end milling of medium carbon steel (S45C) - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry; Alam, S.; Ginta, Turnad Lenggo (2008)
The present paper discusses the development of a mathematical model for predicting the tangential cutting force produced in end-milling operation of medium carbon steel (S45C) using coated TiN insert under dry conditions and full immersion. It is difficult to predict accurately the cutting forces encountered in end milling operations due to large number of independent variables involved. In this work, an approach was undertaken to develop mathematical model for predicting the average tangential cutting force in end milling of S45C in terms of cutting parameters cutting speed, feed rate, and axial depth of cut using design of experiments and the response surface methodology (RSM). All the individual cutting parameters affect on cutting force as well as their interaction are also investigated in this study. The experimental results indicate that the proposed mathematical models suggested could adequately describe the performance indicators within the limits of the factors that are being investigated. The adequacy of the predictive model was verified using ANOVA at 95% confidence level. The developed model shows, based on the variance analysis, that the most influential input parameter was the feed rate followed by axial depth of cut and, finally, by the cutting speed.